Alcohol abuse amongst the youth in Musina Town - Mafa, Prudence (My University, 2019)
Alcohol consumption by young people continues to be a social problem that is associated with major health complications later in life. More youth engage in alcohol consumption frequently with a decreasing age of debut. The current study aimed at exploring and describing the prevalence, patterns and context of youth alcohol consumption in Musina Town, Limpopo Province. A convergence mixed method was employed. This was complemented by an exploratory-descriptive design. Using random stratified and purposive sampling techniques, data was collected from grade 11 learners by way of a survey and a focus group discussion. Data collected from the study show that there is a high prevalence of alcohol use amongst the youth in Musina as almost two thirds (61%) of the survey participants reported to be current alcohol users. Patterns of consumption include drinking during weekends and holidays with binge drinking and drinking until drunkenness being the main forms of alcohol consumption. There was no difference in binge drinking between male and female alcohol drinkers, with 22% of each gender reporting to consume more than five drinks a session. Contexts of alcohol consumption by the youth include drinking at various social gatherings, school, at home, unlicensed liquor outlets, drinking to have fun or as a coping mechanism. Young alcohol consumers have little to no concern about their drinking behaviour, which is exacerbated by alcohol drinking permissive culture and the availability of alcohol. Keywords: Youth, Alcohol consumption, Prevalence, Patterns, Availability
Thesis (M.A.(Social Work)) -- University of Limpopo, 2019
Keywords: Youth; Alcohol consumption; Prevalence; Patterns; Availability; Alcoholism; Drinking of alcoholic beverages -- Musina Town -- Limpopo Province -- South Africa